Nonlinearity And The Random Walk Behaviour Of East Asian Stock Prices - Vun, Methew Kien Chung (2007)

(untitled)
This study examines the price behaviour of East Asian stock markets and individual stocks listed on the Bursa Malaysia in the light of random walk hypothesis by utilizing the new and powerful statistical tool, namely the Brock-Dechert-Scheinkman (BDS) test and Hinich Bispectrum test. This study emphasizes three main objectives. Firstly, this study examines the random walk behaviour and nonlinearity of East Asian stock indices and individual stock return series traded on Bursa Malaysia. Secondly, to ensure the consistency of the results, this study break the full sample period into 5 sub-periods with respect to the financial liberalization and the 1997 Asian financial crisis as the break points to observe whether these two issues will prevent the stocks from randomly pricing or vice versa. Lastly, this study also addresses the issue of whether market size influences the stock price behaviour by comparing the results of large-capitalization stocks and small-capitalization stocks. The following reveal the findings of this study. The econometric investigations (results of BDS) reveal that all the East Asian stock indices and individual stocks listed in the Bursa Malaysia do not follow a random walk process over the full sample period from January 1985 through December 2005. Besides that, the Hinich Bispectrum results reveal that nonlinearity exists in the East Asian stock prices and individual stock prices traded in the Bursa Malaysia. Through the sub-periods analysis, empirical evidence from this study suggests that 1997 Asian financial crisis prevents stock price from following a random walk process. This result comes from the SST (Singapore) and several individual stocks in which pocket of efficiency found before the occurrence of the Asian financial crisis but disappear during and after the crisis period. Lastly, although the analysis on individual stock does not provide any support that market size will influence the stock price randomness, analysis of the East Asian stock indices provide a useful comparison in which, Japan stock market is efficiently performed provide a strong support that market size is a matter of the randomness of the stock prices.